WADAH INTERAKSI DAN KREATIFITAS DIGITAL KREATIF INTERGENERASI - Joshua Junaidi; Rudy Surya (Jurusan Arsitektur dan Perencanaan, 2023)
The Covid-19 pandemic is forcing people to change the norms of working, studying, communicating, up to making transactions or shopping online. This situation encourages further use of integrated internet networks, which causes various new activities and jobs to emerge, followed by spatial designs that can be very different. In this case, is local architecture ready to accommodate changes in digital work styles for different groups of people? This research was created in order to design a place for creative digital interaction that aims to form a community where users can collaborate and grow together. In this case, it is hoped that the older generation can learn from the younger generation who are superior in the digital aspect, as well as how the thoughts of the older generation who have lived longer can inspire the younger generation to create and innovate. This can be achieved through the disprogramming design method, where multiple spatial programs can contaminate one another and could be adapted to various activities. This project is expected to become a casual working space as well as intergenerational education. Keywords: creative digital industry; digital era; disprogramming; intergeneration Abstrak Pandemi Covid-19 memaksa masyarakat merubah norma bekerja, belajar, komunikasi, hingga melakukan transaksi atau belanja secara daring. Keadaan ini mendorong penggunaan jaringan internet yang terintegrasi lebih jauh, yang mana menyebabkan timbulnya pelbagai aktifitas dan pekerjaan baru, diikuti oleh desain keruangan yang bisa menjadi sangat berbeda. Dalam hal ini, apakah arsitektur lokal sudah siapa mewadahi perubahan gaya bekerja digital bagi golongan masyarakat yang berbeda – beda? Penelitian ini dibuat dalam rangka mendesain sebuah tempat interaksi digital kreatif yang bertujuan untuk membentuk sebuah komunitas dimana penggunanya dapat berkolaborasi dan bertumbuh bersama. Dalam hal ini, generasi lansia diharapkan dapat belajar dari generasi muda yang lebih unggul pada aspek digital, juga bagaimana pemikiran generasi lansia yang sudah hidup lebih lama dapat menginspirasi generasi muda dalam berkreasi dan berinovasi. Hal ini dapat dicapai melalui metode perancangan disprogramming, dimana program keruangan yang jamak dapat mengkontaminasi satu sama lain dan dapat disesuaikan dengan berbagai aktivitas. Proyek ini diharapkan dapat menjadi ruang bekerja kasual sekaligus edukasi intergenerasi.